Prevalence of epilepsy in the 15 years and older in Benin: a door-to-door nationwide survey - Yemadje, Luce-Perrine; Houinato, Dismand; Boumédiène, Farid; Ngoungou, Edgar Brice; Preux, Pierre-Marie; Druet-Cabanac, Michel (My University, 2012)
PURPOSE: Estimate the prevalence of epilepsy in the 15 years and older in Benin. METHODS: We used a random multistage sampling design to select a representative sample of the 15 years and older in Benin. From March to May 2010, people were screened door-to-door in the twelve regions of Benin. Screening and data collection were performed using a validated standardised questionnaire of epilepsy in tropical regions. A neurologist examined all people suspected of epilepsy. RESULTS: We identified 174 suspected epilepsy cases from 13,046 screened people; 105 were confirmed by the neurologist (54 men and 51 women). The mean age of PWE was 28.9±14.3 years. The estimate of crude prevalence of epilepsy in the 15 years and older in Benin was 8.05/1000 (95% CI: 6.52-9.58/1000). The crude prevalence of epilepsy among men was 9.77/1000 (95% CI 7.35-12.73/1000) and 6.79/1000 (95% CI 5.06-8.91/1000) for women. The age-adjusted prevalence of epilepsy on sub-Saharan Africa population was 8.25/1000 and 7.33/1000 on world population. Substantial heterogeneity was noted, with differences from one region to another. The most common seizure types were generalised tonic-clonic (80.0%), partial secondary generalised seizures (14.3%) and partial seizures (5.7%). SIGNIFICANCE: This nationwide study is the first in West Africa. It provides a low prevalence of epilepsy in Benin compared to previous studies performed in this country and in neighbouring countries. Restricted-area studies are often motivated by the presence of specific risk factors and could overestimate the prevalence, while large-scale studies could underestimate other subtle forms of epilepsy.
Keywords: epilepsy; 15 years and older; Benin